Weyl transforms associated with the Riemann-Liouville operator - N. B. Hamadi; L. T. Rachdi (International Journal of Mathematics and Mathematical Sciences)
For the Riemann-Liouville transform ℛα, α∈ℝ+, associated with singular partial differential operators, we define and study the Weyl transforms Wσ connected with ℛα, where σ is a symbol in Sm, m∈ℝ. We give criteria in terms of σ for boundedness and compactness of the transform Wσ.